PERBANDINGAN KINERJA KEUANGAN PEMERINTAH DAERAH SEBELUM DAN SETELAH PANDEMI COVID-19 - Riyadi, Adhe Bagus; Bulutoding, Lince; Syariati, Namla Elfa (Universitas Islam Negeri Alauddin Makassar, 2024)
Abstract, This research aims to analyze the comparison of the financial performance of the North Kolaka Regency Regional Government before and after the COVID-19 pandemic. The data used in this research is secondary data obtained from the annual financial reports of the North Kolaka Regency Regional Government for the 2018-2019 and 2021-2022 periods. The data analysis method used is the Paired Sample T-Test hypothesis test to compare the averages of financial variables before and after the COVID-19 pandemic. The research results show that overall there is no significant difference in the financial performance of the North Kolaka Regency Regional Government before and after the COVID-19 pandemic, with a significance value (sig) greater than 0.05. However, there were fluctuations in several financial performance variables between the periods before and after the COVID-19 pandemic. The variables observed include the degree of fiscal decentralization, regional financial dependence, regional financial independence, operating and capital expenditure, efficiency, effectiveness and regional financial growth. Keywords: Degree of fiscal decentralization, regional financial performance, Covid-19 pandemic, regional financial growth, North Kolaka